Cardiac phenotype in familial partial lipodystrophy. (22nd February 2021) - Eldin, Abdelwahab Jalal; Akinci, Baris; da Rocha, Andre Monteiro; Meral, Rasimcan; Simsir, Ilgin Yildirim; Adiyaman, Suleyman Cem; Ozpelit, Ebru; Bhave, Nicole; Gen, Ramazan; Yurekli, Banu; Ozdemir Kutbay, Nilufer; Siklar, Zeynep; et al.
Abstract: Objectives: LMNA variants have been previously associated with cardiac abnormalities independent of lipodystrophy. We aimed to assess cardiac impact of familial partial lipodystrophy (FPLD) to understand the role of laminopathy in cardiac manifestations. Study design: Retrospective cohort study. Methods: Clinical data from 122 patients (age range: 13–77, 101 females) with FPLD were analysed. Mature human induced pluripotent stem cell‐derived cardiomyocytes (hiPSC‐CMs) from a patient with an LMNA variant were studied as proof‐of‐concept for future studies. Results: Subjects with LMNA variants had a higher prevalence of overall cardiac events than others. The likelihood of having an arrhythmia was significantly higher in patients with LMNA variants (OR: 3.77, 95% CI: 1.45–9.83). These patients were at higher risk for atrial fibrillation or flutter (OR: 5.78, 95% CI: 1.04–32.16). The time to the first arrhythmia was significantly shorter in the LMNA group, with a higher HR of 3.52 (95% CI: 1.34–9.27). Non‐codon 482 LMNA variants were more likely to be associated with cardiac events (vs. 482 LMNA : OR: 4.74, 95% CI: 1.41–15.98 for arrhythmia; OR: 17.67, 95% CI: 2.45–127.68 for atrial fibrillation or flutter; OR: 5.71, 95% CI: 1.37–23.76 for conduction disease). LMNA mutant hiPSC‐CMs showed a higher frequency of spontaneous activity and shorter action potential duration. Functional syncytia of hiPSC‐CMs displayed several rhythm alterations such as early afterdepolarizations, spontaneous quiescence and spontaneous tachyarrhythmia, and significantly slower recovery in chronotropic changes induced by isoproterenol exposure. Conclusions: Our results highlight the need for vigilant cardiac monitoring in FPLD, especially in patients with LMNA variants who have an increased risk of developing cardiac arrhythmias. In addition, hiPSC‐CMs can be studied to understand the basic mechanisms for the arrhythmias in patients with lipodystrophy to understand the impact of specific mutations.